2020
DOI: 10.1590/s0100-83582020380100017
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Cabbage Crop to Auxin Herbicides

Abstract: The presence of weeds in cabbage cultivation areas causes a reduction in the productivity and quality of the commercial product. Given the difficulties in management and the scarcity of registered products for weed control in cabbage cultivation, this study aimed to evaluate the tolerance of the cabbage cultivars Astrus Plus to the herbicides 2,4-D and dicamba. Two experiments were performed; one under controlled conditions and another conducted in the field. The efficacy of the herbicides on the initial growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
0
0
Order By: Relevance
“…Consistent with results of this study observed on kale, Nascimento et al (2020) did not report any injury on greenhouse-grown cabbage 'Astrus Plus' (Brassica oleracea var. capitata L.) sprayed with dicamba at 2.4 to 96 g ae ha −1 when plants had two pairs of true leaves.…”
supporting
confidence: 90%
“…Consistent with results of this study observed on kale, Nascimento et al (2020) did not report any injury on greenhouse-grown cabbage 'Astrus Plus' (Brassica oleracea var. capitata L.) sprayed with dicamba at 2.4 to 96 g ae ha −1 when plants had two pairs of true leaves.…”
supporting
confidence: 90%
“…But there was a stimulation of the synthetic auxin in the aerial part, because when it was applied to the soil, there may have been a dilution of its concentration in the liquid part, therefore, doses above four liters of the product started to reduce the height of the plant (Gazola et al, 2019;, However, some plant species can metabolize the 2,4D molecule more efficiently, and thus this molecule is transformed into an original plant molecule. Children produced during auxin synthesis in sensitive eudicots and tolerant monocots showed close responses, but the amount of metabolites produced may vary, and thus results in a lower concentration of tolerant monocots compared to eudicots (Nascimento et al, 2020), where this difference in plant height can be demonstrated in Figure 2. No statistical difference was observed for the leaf area (LA) of peanuts after cultivation in soil with herbicide residue, where the overall average was 8.85.…”
Section: Resultsmentioning
confidence: 97%